The Arab East in the Era of Globalization - Raluca Ioana Oprea (Ovidius University Annals: Economic Sciences Series, 2019)
Although analyzes centered on the subject of globalization have long been a subject, the topic still has a growing interest. The aim of this paper is to analyze the impact of globalization on the Arab East, an area treated marginally in the literature. The set of economic, first of all, but also cultural, religious and political elements, distinguishes this region from the rest of the world. This updated economic outlook, however, can very easily highlight the fact that the East is lagging behind: Arab states are often in conflict and social disorder, civil society structures are largely lacking, political instability is evident in many Arab states. As a result of these deficiencies, the economy of the troubled states remains behind. In other words, economic modernization did not take place in the East as much as in the West.